Relative Age Effect (RAE) Among Malaysia University Athletes - Nor Ashikin Hassan; Zamri Abd. Kahar; Ali Md Nadzalan; Jeffrey Fook Lee Low; Abd Muiz Nor Azmi; Rivan Saghita Pratama; Septyaningrum Putri Purwoto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Currently, most research on RAE in sports is focused on youth and top levels, leaving university athletes, especially in Malaysia, with very little information to work